SEISMIC SEDIMENTOLOGICAL ANALYSIS OF THE LATE MIOCENE SEQUENCES IN THE SMD FIELD, SABAH BASIN, MALAYSIA - NGUI , JIA QI (2020)
A seismic sedimentology study is carried out on the late Miocene sequences of the SMD Field in Sabah Basin. The study attempts to image and interpret the seismic geomorphic features of the subsurface deposits and better visualize the depositional elements of the late Miocene sequences by integrating 3D seismic data and well log data. Seismic attribute analysis is used to enhance the visualization of geomorphic features. Evolution of the geomorphic features were identified and characterized using 3D plan view images at successive time slices. Horizon slices and stratal slices are also used in delineating features on non-horizontal strata. The late Miocene sequences recognized in this study, from oldest to youngest, are termed Unit A to Unit D.